Congenital malformations and use of pesticides in the city of Giruá, RS - Ferreira, Luis Fernando (2020)
The objective of this study was to relate the use of pesticides to the occurrence of congenital malformations in the city of Giruá (RS), as well as to determine the associated risk factors. The research has a quantitative, descriptive-exploratory approach, and was carried out during the first semester of 2019. The study was conducted in two stages: (a) association of the occurrence of malformations with the use of pesticides which was calculated using the Odds Ratios, with the Confidence Interval (CI) being adopted for the 95% samples; and (b) determination of the associated risk factors, for which an interview was conducted with farmers living in the municipality. It is noticed that the rates of congenital malformations in the city of Giruá, are higher than the state average for the same period. There is a probability that the occurrence of malformations in the municipality is associated with the use of pesticides, because all Odds Ratios were greater than one. The risk factors identified were low educational level, toxicological class and active principles, inadequate use of Personal Protective Equipment (PPE), number of people diagnosed with intoxication or who reported some associated signal or symptom and storage of the products.